The Role of the Magetan Police Traffic Dikmas in Preventing Traffic Accidents Among High School Students - Su’aad, Daffa Al Malik (Advances in Police Science Research Journal, 2024)
The development of technology is something that has a big influence on human life, including transportation technology which has changed from simple to complex so that it can be more efficient. The importance of transportation has resulted in people meeting their transportation needs independently and resulting in the number of vehicles continuing to increase. The rapid increase in the number of vehicles has caused traffic problems in Magetan Regency, namely traffic accidents which continue to increase every year, especially among students. In this case, pre-emptive police action is very necessary to prevent accidents by providing an understanding of traffic safety through direct community service activities by the South Kalimantan Unit. The results of this research indicate that community education activities carried out by the South Kalimantan Unit have obstacles from within and outside the organization. This results in the delivery of material not being optimal and on target in providing understanding to high school students regarding traffic rules and safety.